The Reality of Administrative Empowerment of Women Leaders to Participate in Decision-making: An Exploratory Study on Governmental Entities - Alzahrani, Tariq Saleh; Almalki, Majd Abdullah; Jifri, Ali Omar (The Arab Journal of Administration, 2025)
The aim of this study is to identify the reality of the administrative empowerment of women leaders involved in decision-making in government bodies and to explore methods, methods and tools to support such practices in order to determine the impact and reality of such empowerment in light of the growing and accelerating leadership and social diversity in various organizations and sectors and the Kingdom’s ambitious vision 2030, The objective of the researcher was to explore this reality, using the descriptive and analytical approach, in accordance with the questionnaire, to collect study data by applying to a sample of the female leadership community in 95 governmental Entities, according to the official number announced at the National Government Platform. The sample numbered 150 women leaders and a proactive sample of 25 female administrators of the General Statistics Authority was conducted from a director of administration and a senior director to a vice-president, It expresses the various leadership nomenclature on the main sample of the study from a managing director and higher to be a meaningful study of that reality after going beyond all the observations of the proactive reconnaissance procedure. The researcher examines the axes of managerial empowerment and participation in decision-making in several dimensions distributed over the study, namely powers, human and material resources, organizational culture, training, and qualification, to be the highlight of its outputs leading to the exploration of the most visible strengths in the reality of empowerment and how it can be improved and enhanced to serve studies, research, and management and leadership literature.